A new species of Cryptocentrus (Teleostei: Gobiidae) from northern Taiwan - Chen, I-Shiung; Yang, Yen-Cheng (Zootaxa, 2024)
A new marine, shrimp-associated goby of Cryptocentrus was discovered from the coastal waters of New Taipei City, Taiwan but it is very rare merely with three adult specimens. The new species, Cryptocentrus taiwanensis n. sp. can be well distinguished from all other congeners by the unique combination of the following features: (1) fins: second dorsal fin rays I/11; anal fin rays I/10; pectoral fin rays 16; (2) squamation: longitudinal scale series 100–101, transverse scale rows 29–31, perdorsal scales 15–17; (3) vertebral count 26; (4) head canal pores: anterior oculoscapular canal with terminal pore σ; single pore λ; lateral section of anterior oculoscapular canal with three pores α, β and ρ; posterior oculoscapular canal with two pores θ, τ; preopercular canal present with three pores γ, δ and ε; sensory papillae: 5 major transverse rows of infraorbital region; (4) rear edge of mouth: extending beyond the vertical of rear margin of pupil in male and (5) specific coloration: body scattered with many white spots and a middle longitudinal row of 8 blackish brown blotches, second dorsal fin with vertical blackish brown bars on branched rays on distal half, anal fin with three horizontal rows of blackish brown blotches and connected to stripe in middle row, caudal fin translucent radiating with thick blackish stripes in middle 1/3 region in male. The brief morphological comparison with its own related species would be also addressed.